Abiotic Stress Signaling and Responses in Plants - Zhu, Jian-Kang (Cell, 2016)
As sessile organisms, plants must cope with abiotic stress such as soil salinity, drought, and extreme temperatures. Core stress-signaling pathways involve protein kinases related to the yeast SNF1 and mammalian AMPK, suggesting that stress signaling in plants evolved from energy sensing. Stress signaling regulates proteins critical for ion and water transport and for metabolic and gene-expression reprogramming to bring about ionic and water homeostasis and cellular stability under stress conditions. Understanding stress signaling and responses will increase our ability to improve stress resistance in crops to achieve agricultural sustainability and food security for a growing world population. Understanding the core set of pathways that allow plants to cope with abiotic stresses such as salinity, drought, and extreme temperatures can allow us to improve crop sustainability and food security for a growing world population.